2023
DOI: 10.1038/s41597-023-02119-w
|View full text |Cite|
|
Sign up to set email alerts
|

An inventory of native-alien populations in South Africa

Abstract: Species can be both native and alien to a given administrative region. Here we present the first consolidated inventory of these ‘native-alien populations’ for South Africa, and provide an overview of the data it contains. To gather data, literature searches were performed and experts were consulted both directly and via an on-line survey. Putative native-alien populations were then scored based on a newly developed protocol. The final inventory contains information on 77 native species from 49 families across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…The widespread distribution of Pueraria montana, L. camara, and A. donax highlights the gap between the local authorities (local municipalities and government institutions) and institutions in managing invasive alien species in the urban area (Figure 6d-f). Seven newly reported native-alien populations recorded in this study will add to the list of native-alien populations in South Africa reported by Nelufule et al [47]. Two of these species were shared between the two sampling sites, namely, Aptenia cordifolia and Tephrosia grandiflora, while five other species were recorded only within the university campus.…”
Section: Species Compositionsupporting
confidence: 60%
See 3 more Smart Citations
“…The widespread distribution of Pueraria montana, L. camara, and A. donax highlights the gap between the local authorities (local municipalities and government institutions) and institutions in managing invasive alien species in the urban area (Figure 6d-f). Seven newly reported native-alien populations recorded in this study will add to the list of native-alien populations in South Africa reported by Nelufule et al [47]. Two of these species were shared between the two sampling sites, namely, Aptenia cordifolia and Tephrosia grandiflora, while five other species were recorded only within the university campus.…”
Section: Species Compositionsupporting
confidence: 60%
“…Seven newly reported native-alien populations recorded in this study will add to the list of native-alien populations in South Africa reported by Nelufule et al [ 47 ]. Two of these species were shared between the two sampling sites, namely, Aptenia cordifolia and Tephrosia grandiflora , while five other species were recorded only within the university campus.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Although in this study there were few lost reports for Common mynas and Common starlings, their population may likely integrate with those already outside captivity and establish further populations, given their potential distribution patterns in South Africa and elsewhere [15,36,56,72,73]. Furthermore, the identification of the native-alien populations in South Africa [74] indicates a rise in the within-country dispersal of native bird species facilitated by the pet trade. For example, there have been reports of pet escapees of Rosyfaced and Fischer's lovebirds in South Africa, particularly in the Gauteng region [34,36,75].…”
Section: Patterns In Case Reports and Species Trendsmentioning
confidence: 81%